Judicialização da política e ativismo judicial : estudo dos motivos determinantes e limites da interpretação judicial - Alencar Filho, José Geraldo (2011)
Changes after the great world wars, especially the bad things caused by German's Third Reich caused an upheaval in the study and application of legal standards. The fear that Law could be used as a tool capable of inflicting such horrors fostered the establishment of Constitutional Courts besides the development of the American judicial review of judicial construction of Law, that also spread during this time its ideals of democracy and the application of rules to the rest of the world. The model of the welfare and democratic state brings new rights, especially of a fundamental basis and the institutes of political intervention in judges decision-making when established only by the Legislative and Executive Powers put into question the state of the triple division of power, created under the liberal state and it no longer can explain the reality of an interventionist state that brings the danger of government of the toga . Among the propellers of this effervescence of the Judiciary Power there are the globalization, the concepts of post-modernity with the breach of all paradigms on modern age; the failure of Cartesianism based on the concepts of positivism due to law enforcement with the breaching of the myth of neutrality , inertia and impartiality of the judiciary; besides the violation of the theory that the judge does not create law able to innovate the legal system beyond the Neo constitutionalism and the freedom of interpretation of the law especially those ones of Constitutional Law, those as we said are allies to the fact that there is judicialization and there is a pro active of the judges behavior in the direction of judicial proceedings. The existence of open laws and a set of principles allied with the failure of the Legislative Power with the sense of crisis in the statutory law and the performance of the Executive Power cannot effect rights and gave judges the power to increase their jurisdiction enlarging their boundaries. So, it is necessary to consider alternatives to solve conflicts that may arise with this phenomena. Especially those ones connected to the needy of controlling the interpretation done by the judges, setting limits and also to the fact that the questioning of legitimacy of their decisions to the lack of democratic instruments of analysis and the lack of popular legitimacy through suffrage bringing the explanation of the subjectivist and procedural theories. In addition to this the ideas developed by Dworkin and Viehweg as possible solution to solving the problem of hard cases and legislative gaps. It is necessary to think about the lasting or eternity of concepts of the Legalization of Judicial Activism in societies emerging from this new reality